Exploring the potential roles and services of the community pharmacy team during a time of healthcare reform - Karsan, Yasmin (2021)
Globally, health systems are complex and dynamic and can face issues when attempting to deliver equitable, accessible healthcare. Much of this is due to lack of integration across care providers. The National Health Service in the United Kingdom has revolutionised healthcare as we know it today. Currently, the NHS can be perceived as significantly fragmented, with many care providers delivering services in duplication.